The Cancer-Testis Long Non-coding RNA PCAT6 Facilitates the Malignant Phenotype of Ovarian Cancer by Sponging miR-143-3p - Tan, Xiaofang; Shao, Yang; Teng, Yue; Liu, Siyu; Li, Weijian; Xue, Lu; Cao, Yuepeng; Sun, Chongqi; Zhang, Jinhong; Han, Jing; Wu, Xiaoli; Xu, Hanzi; et al. (Frontiers in Cell and Developmental Biology, 2021)
Background: It has been reported that long noncoding RNAs (lncRNAs) play critical roles in tumorigenesis. However, the underlying mechanism of ovarian cancer (OC) remains to be elucidated. The aim of this study was to uncover the function and underlying mechanisms of PCAT6 in OC. Methods: The expression pattern of PCAT6 in ovarian cancer was analysed in the GSE137238, GSE143897 and Gene Expression Profile Interactive Analysis (GEPIA) datasets. Kaplan–Meier Plotter online software was used for survival analysis. Loss-of-function assays and gain-of-function assays were used to assess the function of PCAT6 in OC development. Moreover, small-RNA sequencing, bioinformatic analysis, luciferase assay and rescue experiments were carried out to clarify the potential mechanism of PCAT6 in OC. Results: PCAT6 was significantly increased in OC tissues and positively correlated with advanced stages, poor overall survival, progression-free survival and post-progression survival. Overexpression of PCAT6 in A2780 and SKOV3 cells promoted OC cell proliferation, migration and invasion. In contrast, knockdown of PCAT6 exhibited the opposite effects on OC cells. Notably, PCAT6 could bind to miR-143–3p and affect the expression of kinase transforming growth factor (TGF)-β-activated kinase 1 (TAK1). Subsequent rescue assays confirmed that upregulation of miR-143-3p decreased the PCAT6 overexpression-induced promotion of proliferation, migration and invasion in A2780 and SKOV3 cells. Moreover, downregulation of miR-143-3p reversed the PCAT6 knockdown-induced decrease in proliferation, migration and invasion in the two cell lines. Conclusions: Our findings demonstrate that PCAT6 plays an oncogenic role in OC and may be used as a potential therapeutic target for treating OC.